PENGARUH SERTIFIKASI GURU TERHADAP KINERJA DAN PROFESIONALISME GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI UPTD SDN 122340 JALAN SIPIROK - Simanjuntak, Melvin; Ilni Yoana Payunda Br Siahaan; Nurintan Hutapea; Herlina Tinambunan; Melissa Lubis; Rolekson Samosir; Angelin Hutahaean; Jenny Ramaito Br. Rumahorbo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teacher certification is very important for teachers to show their professionalism as educators or teachers, especially in Indonesia, and this certification can support teacher welfare. This article aims to determine the role of teacher certification on the performance and professionalism of teachers teaching in the classroom in improving the quality of learning. This study uses a quantitative approach, descriptive methods to determine the population or sample is done randomly and data collection techniques using research instruments. Therefore, the main data used in this study are in the form of numbers. Data collection techniques through questionnaires, observations, documentation and literature studies. The results of the study indicate (1) that teacher certification has a positive effect on teacher performance (2) teacher certification has a positive effect on teacher professionalism, (3) teacher certification has a positive effect on improving the quality of learning in the classroom. From the results of writing this article, it can be concluded that teacher certification has great potential to improve the quality of education at UPTD SD Negeri 122340 Jl. However, to achieve optimal results, efforts need to be made to overcome various challenges and obstacles in the implementation of the certification program by improving the quality of training, building a strong support system, and increasing teacher awareness, it is hoped that teacher certification can be one of the important factors in improving the quality of learning. at UPTD SD Negeri 122340 Jl. Sipirok.